2021
DOI: 10.1080/02813432.2021.1882082
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ experiences of video consultation with patients at a public virtual primary care clinic: a qualitative interview study

Abstract: Objective: To describe physicians' experiences of video consultation with new patients visiting a publicly owned virtual primary care clinic. Design: In this qualitative study, data were collected from semi-structured individual interviews and analysed by systematic text condensation. Setting: A publicly owned virtual primary care clinic in Region V€ astra G€ otaland, Sweden. Subjects: Ten primary care physicians working at the clinic. Results: Connecting with a patient over video could be either straightforwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 28 publications
7
77
0
2
Order By: Relevance
“…Focusing on the context of Swedish primary care, three different studies recently found that physicians considered the types of telemedicine evaluated to be suitable for some patients and questions, but not for all. 35–37 This compares well to our category “Useful under certain conditions”, underlining the need for implementation in cooperation with the profession.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Focusing on the context of Swedish primary care, three different studies recently found that physicians considered the types of telemedicine evaluated to be suitable for some patients and questions, but not for all. 35–37 This compares well to our category “Useful under certain conditions”, underlining the need for implementation in cooperation with the profession.…”
Section: Discussionsupporting
confidence: 60%
“…Findings include increased efficiency and more precise communication, but also reports of overuse, information overload, and misinterpretations. [33][34][35][36][37] While most papers cover specific tools, PCPs' overall views and experiences of telemedicine have been little studied, and not at all in a Swedish context. Consequently, in 2019, we conducted a web-based survey regarding telemedicine among PCPs in southern Sweden.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…The categories will be used as subheadings further on, the results related to each of them will be presented and explained in more detail. (Tables 3, 4, and 5) Flexibile working hours and/or place (13,37,39,(45)(46)(47) Saved travel time/costs (39,41,47) Feeling more relaxed and at ease (39,45)…”
Section: General Characteristics Of the Reviewed Studiesmentioning
confidence: 99%
“…Convenience (46,47) Reduced workload (37,39) E ciency Shorter visits (13,48,49,54) Increased productivity/e ciency (35,37,39,41,45,48,50,51) Satisfaction Overall positive experience (13,35,40,41,43,44,46,47,49,(51)(52)(53)(54) Easy to learn how to use (41,44) Easy to use (13,39,(41)(42)(43)47,49,51,(53)(54)(55)(56) Satisfaction with the system/platform and/or its features (13,47,48,52) Comfortable to treat patients via digital care visits (39,48) The interaction between healthcare professional a...…”
Section: General Characteristics Of the Reviewed Studiesmentioning
confidence: 99%
See 1 more Smart Citation